Interactions between substrate temperature and humidity in signalling cyclical dormancy in seeds of two perennial tropical species - Duarte, Daniela M.; Garcia, Queila S. (Seed science research, 2015)
The involvement of environmental factors in dormancy cycling is well known in temperate annual species, but it is not known how interaction between soil temperatures and humidity can modulate dormancy in perennial tropical species. In this study the effects were evaluated of substrate temperature and humidity on the modulation of the acquisition and overcoming of secondary dormancy in the buried seeds of two endemic Eriocaulaceae species from the rocky fields (campos rupestres) vegetation in south-eastern Brazil. Fresh seeds of Comanthera bisulcata and Syngonanthus verticillatus were buried and subsequently maintained at temperatures of 15, 20, 25 and 30°C, under three substrate humidity levels (boggy, humid and humid/dry). The seeds were exhumed every 3 months and tested for germination (20°C, 12 h photoperiod) and viability (tetrazolium test). The seeds of both species acquired dormancy after burial in all of the treatments. During the experimental period they demonstrated cycles of acquisition and overcoming of dormancy that were most evident in the treatments involving alterations of the substrate humidity (humid/dry regime) that coincided with the environmental conditions found naturally in the region of origin of the species. The seeds gradually lost dormancy during the dry period and re-acquired it when exposed again to humidity; dormancy would once again be overcome during the subsequent dry period. Burial promoted the acquisition of dormancy in C. bisulcata and S. verticillatus seeds; the lowest temperature tested favoured overcoming dormancy; and varying the humidity regime signalled the acquisition and the overcoming of secondary dormancy.